Optimizing Bioremediation: Elucidating Copper Accumulation Mechanisms of Acinetobacter sp. IrC2 Isolated From an Industrial Waste Treatment Center - Irawati, Wahyu; Djojo, Eric Santoso; Kusumawati, Lucia; Yuwono, Triwibowo; Pinontoan, Reinhard (Frontiers in Microbiology, 2021)
Acinetobacter sp. IrC2 is a copper-resistant bacterium isolated from an industrial waste treatment center in Rungkut, Surabaya. Copper-resistant bacteria are known to accumulate copper inside the cells as a mechanism to adapt to a copper-contaminated environment. Periplasmic and membrane proteins CopA and CopB have been known to incorporate copper as a mechanism of copper resistance. In the present study, protein profile changes in Acinetobacter sp. IrC2 following exposure to copper stress were analyzed to elucidate the copper resistance mechanism. Bacteria were grown in a Luria Bertani agar medium with and without CuSO4 supplementation. Intracellular copper ion accumulation was quantified using atomic absorption spectrophotometry. Changes in protein profile were assessed using sodium dodecyl sulfate polyacrylamide gel electrophoresis. The results showed that 5 mM CuSO4 was toxic for Acinetobacter sp. IrC2, and as a response to this copper-stress condition, the lag phase prolonged to 18 h. It was also found that the bacteria accumulated copper to a level of 508.01 mg/g of cells dry weight, marked by a change in colony color to green. The protein profile under copper stress was altered as evidenced by the appearance of five specific protein bands with molecular weights of 68.0, 60.5, 38.5, 24.0, and 20.5 kDa, suggesting the presence of CopA, multicopper oxidase (MCO), CopB, universal stress protein (Usp), and superoxide dismutase (SOD) and/or DNA-binding protein from starved cells, respectively. We proposed that the mechanism of bacterial resistance to copper involves CopA and CopB membrane proteins in binding Cu ions in the periplasm and excreting excess Cu ions as well as involving enzymes that play a role in the detoxification process, namely, SOD, MCO, and Usp to avoid cell damage under copper stress.